Does Modern Lifestyle Favor Neuroimmunometabolic Changes? A Path to Obesity - Marques, Camila Guazzelli; dos Santos Quaresma, Marcus V. L.; Nakamoto, Fernanda Patti; Magalhães, Ana Carolina Oumatu; Lucin, Glaice Aparecida; Thomatieli-Santos, Ronaldo Vagner (Frontiers in Nutrition, 2021)
Factors linked to modern lifestyles, such as physical inactivity, Western diet, and poor sleep quality have been identified as key contributors to the positive energy balance (PEB). PEB rises adipose tissue hypertrophy and dysfunction over the years, affecting cells and tissues that are metabolically critical for energy homeostasis regulation, especially skeletal muscle, hypothalamic-pituitary-adrenal axis, and gut microbiota. It is known that the interaction among lifestyle factors and tissue metabolic dysfunction increases low-grade chronic systemic inflammation, leading to insulin resistance and other adverse metabolic disorders. Although immunometabolic mechanisms are widely discussed in obesity, neuroimmunoendocrine pathways have gained notoriety, as a link to neuroinflammation and central nervous system disorders. Hypothalamic inflammation has been associated with food intake dysregulation, which comprises homeostatic and non-homeostatic mechanisms, promoting eating behavior changes related to the obesity prevalence. The purpose of this review is to provide an updated and integrated perspective on the effects of Western diet, sleep debt, and physical exercise on the regulation of energy homeostasis and low-grade chronic systemic inflammation. Subsequently, we discuss the intersection between systemic inflammation and neuroinflammation and how it can contribute to energy imbalance, favoring obesity. Finally, we propose a model of interactions between systemic inflammation and neuroinflammation, providing new insights into preventive and therapeutic targets for obesity.